Multilocus characterization and phylogenetic analysis of Leishmania siamensis isolated from autochthonous visceral leishmaniasis cases, southern Thailand - Leelayoova, Saovanee (BioMed Central, 2013)
BACKGROUND: Visceral leishmaniasis (VL) caused by Leishmania siamensis is an emerging disease continuously reported in six southern provinces of Thailand. To date, the phylogenetic relationships among Leishmania isolates from Thai patients and other Leishmania species are still unclear and the taxonomic diversity needs to be established. In this study, the phylogenetic inference trees were constructed based on four genetic loci (i.e., SSU-rRNA, ITS1, hsp70, and cyt b), using DNA sequences obtained from autochthonous VL patients from southern Thailand and reference sequences of reported Leishmania isolates from other studies deposited in GenBank. RESULTS: Phylogenetic analyses of hsp70 and cyt b loci supported a clade comprised of L. siamensis isolates, which is independent to the other members in the genus Leishmania. In combination with genetic distance analysis, sequence polymorphisms were observed among L. siamensis isolates and two different lineages could be differentiated, lineages PG and TR. Phylogenetic analysis of the cyt b gene further showed that L. siamensis lineage TR is closely related to L. enrietti, a parasite of guinea pigs. CONCLUSION: The finding of this study sheds further light on the relationships of L. siamensis, both in intra- and inter-species aspects. This information would be useful for further in-depth studies on the biological properties of this important parasite.